A manual physical therapy approach versus subacromial corticosteroid injection for treatment of shoulder impingement syndrome: a protocol for a randomised clinical trial. Issue 2 (24th September 2011) - Rhon, Daniel I; Boyles, Robert E; Cleland, Joshua A; Brown, David L
Abstract : Introduction: Corticosteroid injections (CSI) are a recommended and often-used first-line intervention for shoulder impingement syndrome (SIS) in primary care and orthopaedic settings. Manual physical therapy (MPT) offers a non-invasive approach with negligible risk for managing SIS. There is limited evidence to suggest significant long-term improvements in pain, strength and disability with the use of MPT, and there are conflicting reports from systematic reviews that question the long-term efficacy of CSI. Specifically, the primary objective is to compare the effect of CSI and MPT on pain and disability in subjects with SIS at 12 months. Design: This pragmatic randomised clinical trial will be a mixed-model 2×5 factorial design. The independent variables are treatment (MPT and CSI) and time with five levels from baseline to 1 year. The primary dependent variable is the Shoulder Pain and Disability Index, and the secondary outcome measures are the Global Rating of Change and the Numeric Pain Rating Scale. For each ANOVA, the hypothesis of interest will be the two-way group-by-time interaction. Methods and analysis: The authors plan to recruit 104 participants meeting established impingement criteria. Following examination and enrolment, eligible participants will be randomly allocated to receive a pragmatic approach of either CSI or MPT. The MPT intervention will consist of six sessions, and the CSI intervention will consist of one to three sessions. All subjects will continue to receive usual care. Subjects will be followed for 12 months. Dissemination and ethics: The protocol was approved by the Madigan Army Medical Center Institutional Review Board. The results may have an impact on clinical practice guidelines. This study was funded in part by the Orthopaedic Physical Therapy Products Grant through the American Academy of Orthopaedic Manual Physical Therapists. Trial Registration: http://clinicaltrials.gov/ NCT01190891 .